The Effect of Picture Series Towards Students’ Writing Skill In Recount Text at The Eighth Grade Students’ of SMPN 6 Malingping Lebak-Banten - Asriani Asriani; Rizdki Elang Gumelar; Tatu Munawaroh (Journal of English Language Learning, 2022)
This research paper aim to investigate the effect of picture series towards students’ writing skill in recount text at the eighth grade students’ of SMPN 6 Malingping Lebak Banten in academic year 2021/2022. The method used in this research was quantitative method. The design of this research was quasi-experimental design and cluster random sampling: the researcher used VIII A (20 students) as class experimental and VIII B (20 students) as class control. In the collecting data technique, the researcher used pre-test and post-test. The analysis data used to test research hypotheses using SPSS 25.0 is test of paired samples test. The results of the research concluded that there are a significant effect of picture series towards students’ writing skill in recount text with a significant value (p-value) = 0.000. They are < α = 0.05. The results of the research indicate that the hypotheses is accepted. According to the criteria of the test, it could be concluded that there was was progress in the effect of picture series towards students’ writing skill in recount text at the eighth grade students’ SMPN 6 Malingping Lebak Banten was effective